Diseño y construcción de una máquina troqueladora en frío para la construcción de paneles metálicos. - Loaiza Andrade, Henry Fabricio (2013)
The die cutting allows us to perform various types of parts and processes such as stamping, bending, cutting, etc. To obtain pieces by punching process requires a hydraulic or mechanical system by means of which the necessary force is achieved for the stamping of steel plates with the shape of the dies used. This thesis project aims to determine the parameters necessary to design and build a prototype of a machine efficient punch considering factors such as: verifying the quality of the final product, so as to see the impact of this product in the local environment. Besides building a punch machine to operate in any working condition considering technical and economic parameters. These jobs are performed only in two cities in our country, resulting in delay in the delivery of the panels and the cost is very high. This thesis defines the parameters of design and operation of a prototype of a machine punch for the construction of metal panels, then built and checked for proper operation.